Drug review: Ibrutinib - Parathan Karunakaran (Indian Journal of Medical and Paediatric Oncology)
Ibrutinib is an irreversible BTK inhibitor, characterized by high selectivity and potency. It has revolutionized the therapy of B-cell lymphomas, especially chronic lymphocytic leukemia (CLL) and mantle cell lymphoma. Importantly, it has expanded the armamentarium for those patients who are refractory to conventional chemoimmunotherapy. This small-molecule inhibitor has shown efficacy in this difficult-to-treat subset – those with del(17p)/TP53-mutated CLL. Its immunomodulatory properties make it an excellent choice for combining with other immunotherapeutic agents such as venetoclax. The drug is not without drawbacks. The need for indefinite therapy and the presence of adverse effects such as infection, bleeding, hypertension, and arrhythmia temper our enthusiasm for this versatile drug. But overall, ibrutinib's favorable risk profile and lack of myelosuppression make it an ideal therapy for the elderly and those with multiple comorbidities.